Physiological effects of vigorous exercise performing on unstable support - Orlova E. A. (Scientific community of students, 2016)
in this research the author investigates the question of series of press-up execution influence at unstable platform on myographic indexes of muscle work at corpus and shoulder girdle and also 6-week training including this exercise on unstable support and its influence on the growth dynamics of force abilities. As the author marks, 10 students of a sport high school took part in the research. They registrated electromyogram from 6 muscles while performing a set of 10 press-ups at stable and unstable platform. The same exercise was has been working out during 6 weeks to develop force endurance. Before and after trainings the respondents carried out tests in the exercise press-up "to the limit" and on press of a stationary cross-bar at tenzoplatform to registrate maximum arbitrary force. After 6 weeks of training the trainees definitely improved their indicators of their force endurance and arbitrary force.
Keywords: силовые способности; студенты спортивного вуза; неустойчивая опора; электромиограмма; тренировка силовой выносливости; мышцы туловища; мышцы плечевого пояса; force abilities; sport high school students; unstable support; electromyogram; force endurance training; corpus muscles; shoulder girdle muscles